Seasonal cycles in the housing market - Cemil Selcuk (Cardiff University, Cardiff Business School, 2012)
The housing market exhibits a puzzling yet repetitive seasonal boom and bust cycle where prices and trade volume rise in summers and fall in winters. This paper presents a search model that analytically generates the observed deterministic cycle.
Keywords: D39; D49; D83; 330; housing; search; thin and thick markets; seasonality